2022
DOI: 10.1002/adfm.202113274
|View full text |Cite
|
Sign up to set email alerts
|

Information Storage Based on Stimuli‐Responsive Fluorescent 3D Code Materials

Abstract: With the booming of information technology, considerable progress has been witnessed in information storage carriers, accompanied by soaring storage capacity. 3D codes as an emerging information storage carrier has attracted wide attention. However, it is challenging for conventional 3D codes to transform their encoded information, restricting their applications. Due to their rich color characteristics and various stimuli responsiveness, fluorescent materials can be utilized to construct stimuli-responsive 3D … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(37 citation statements)
references
References 137 publications
(207 reference statements)
1
36
0
Order By: Relevance
“…Fluorescent polymeric hydrogels (FPHs) are rising stars of luminescent materials that can combine the merits of traditional fluorescent polymers and hydrogels, including responsive fluorescence, tissue-like modulus, intrinsic soft wet nature and so on. [1][2][3][4][5][6] These advantages make FPHs potentially applicable for wide applications ranging from bioimaging and sensing 7,8 to information encryption [9][10][11] and soft robotics. [12][13][14][15] The past two decades have witnessed the development of numerous FPHs on the basis of organic fluorophores, [16][17][18][19][20][21][22][23][24] luminescent metal complexes [25][26][27][28][29][30][31][32] and nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Fluorescent polymeric hydrogels (FPHs) are rising stars of luminescent materials that can combine the merits of traditional fluorescent polymers and hydrogels, including responsive fluorescence, tissue-like modulus, intrinsic soft wet nature and so on. [1][2][3][4][5][6] These advantages make FPHs potentially applicable for wide applications ranging from bioimaging and sensing 7,8 to information encryption [9][10][11] and soft robotics. [12][13][14][15] The past two decades have witnessed the development of numerous FPHs on the basis of organic fluorophores, [16][17][18][19][20][21][22][23][24] luminescent metal complexes [25][26][27][28][29][30][31][32] and nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12] Among these, luminescent polymers have attracted much attention due to their unique optical properties and wide range of applications, including smart displays, [13][14][15] optical sensing, 16,17 soft luminescent actuation, 18,19 information storage, and anticounterfeiting. [20][21][22][23] These materials usually show a change in optical properties in response to an external stimulus (e.g., pH, solvent, temperature, ions, and light). [24][25][26][27] Great efforts have been devoted to designing and developing stimuli-responsive materials.…”
Section: Introductionmentioning
confidence: 99%
“…Luminescence materials with the ability to encode and decode information have been widely used in many fields like printable ink, labels, and modern currency. From monochrome to polychromatic and panchromatic, various tunable luminescence materials regulated by excitation light, chemical reagents, luminescence lifetime, heat, and other stimuli are developed to realize advanced luminescence materials. Liu et al reported four-level luminescence anti-counterfeiting technology based on two kinds of colorless anti-counterfeiting inks which display fluorescence with different colors, intensity, and lifetime by the irradiation of UV and NIR . However, the preparation process is always complex and costly, and sometimes the color change is momentary and requires specific methods or devices to detect.…”
Section: Introductionmentioning
confidence: 99%